Adaptive reliable output tracking of networked control systems against actuator faults. Issue 9 (June 2017) - Sakthivel, R.; Selvaraj, P.; Lim, Yongdo; Karimi, H.R.
Abstract: This paper investigates the reliable adaptive observer-based output tracking control problem for a class of networked control systems subject to actuator faults and external disturbances via equivalent-input disturbance technique. Notably, the reliable control design based on adaptive mechanism is implemented to compensate the on-line actuator faults automatically and an observer-based controller is introduced through communication networks to drive the output of controlled plant to track the output of a reference model. Moreover, due to the effect of network-induced delays and packet dropouts in the controller-to-actuator channel, the inputs of controlled plant and observer-based tracking controller are updated in an asynchronous way. Then, based on the asynchronous characteristic, the resulting closed-loop networked control system is formulated with two interval time-varying delays for obtaining the required result. In particular, the equivalent-input disturbance approach improves the disturbance rejection performance and it does not require any prior knowledge of the disturbances. By constructing a suitable Lyapunov–Krasovskii functional and using free-weighting matrix approach, a new set of sufficient conditions for the solvability of the addressed problem is derived in terms of linear matrix inequalities. At last, the proposed result is validated through two numerical examples and also a comparison study is presented which shows the effectiveness of the developed control scheme over some existing conventional control schemes.